Philipp Blom, "Subjugate the Earth: The Beginning and End of Human Domination of Nature" - Leiss, William (Journal for the study of religion, nature and culture, 2025)
Philipp Blom, Subjugate the Earth: The Beginning and End of Human Domination of Nature (Cambridge: Polity Press, 2025) xxv + 303 pp., $ 30.00 (pbk), ISBN: 978-1-509-56132-2. (Translation of the German original, Munich 2022).